15 Cardiac magnetic resonance imaging in end stage renal disease using T1 and feature-tracking. (18th April 2016) - Rutherford, E; Mangion, K; McComb, C; Talle, M; Struthers, AD; Berry, C; Mark, PB
Abstract : Introduction: Premature cardiovascular death is the leading cause of mortality amongst End Stage Renal Disease (ESRD) patients. Imaging myocardial fibrosis in ESRD is challenging as gadolinium contrast agent use is contraindicated. Global longitudinal strain (GLS) and native T1 relaxation time may be more informative than ejection fraction (EF) in this patient group. Methods: 33 haemodialysis patients and 28 matched healthy controls underwent CMR at 3T (Magnetom Verio, Siemens, Erlangen, Germany). GLS, strain rate (SR) and early diastolic strain rate (EDSR) were calculated using feature-tracking software (Diogenes Image Arena, Munich, Germany). T1 maps were acquired using an optimised MOLLI investigational prototype sequence (Siemens Healthcare WIP 448). Global (GT1), septal (ST1) and mid-septal (MST1) T1 times were calculated. Results: Indexed LVM (LVMI), T1 (Figure 1 ) and GLS values were higher in ESRD (Table 1 ). In ESRD patients T1 values positively correlated with LVMI (GT1 r 2 0.204 p = 0.008, ST1 r 2 0.201 p = 0.009, MST1 r 2 0.248 p = 0.003). Septal T1 values also positively correlated with end diastolic volumes (ST1 r 2 0.145 p = 0.029, MST1 r 2 0.213 p = 0.007). GLS also positively correlated with LVMI (GLS r 2 0.426 p = 0.013). Lower EDSR and SR tended to correlate with higher LVMI although this did not reach statistical significance (EDSR r 2 −0.342 p = 0.051, SR r 2 −0.327 p = 0.063). Conclusions: In ESRD patients, T1 relaxation times correlate with LV mass indices and end diastolic volumes, features associated with adverse outcome. GLS may be associated with adverse outcomes as it correlates with LVMI. Further work is required to explore the relationship between strain, T1 and their prognostic implications in ESRD patients.